IMPLEMENTASI DIFFERENSIASI DALAM PERSPEKTIF KONTRUKTIVISME PADA MATA PELAJARAN MATEMATIKA - Nurhasanah, Aan; Yuliyanti, Novi; Citrawati, Tyasmiarni; Sukamto, Sukamto; Handoyo, Eko; Raharjo, Tri Joko (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2024)
This research aims to explore in depth the experiences, perceptions and views of teachers and students regarding the implementation of differentiated learning in mathematics learning based on constructivist principles. The research method uses a qualitative approach by collecting data from interviews and classroom observations. The research subjects consisted of 7 teachers and 30 students. Data analysis was processed using triangulation techniques from various sources, namely teachers, students and curriculum documents. The results of the research show that the implementation of differentiated learning is effective in increasing individual students' understanding of mathematical concepts, giving teachers the freedom to prepare various plans, implementing varied learning strategies, and students gaining new understanding through the construction of their learning experiences. with  students constructing their own understanding so as to enable them to achieve their learning potential optimally.